Training New DMC Members: A Call to Action - Rockhold, Frank; Mahaffey, Kenneth; DeMets, David (Therapeutic innovation & regulatory science, 2024)
Historically, clinical trialists developed DMC expertise and experience with “on the job training”. Clinical trialists have recognized a large and growing gap between the demand and supply of trained DMC members due in part to the huge increase in ongoing clinical trials. A critical need exists to increase the supply of DMC trained clinicians and biostatisticians. Despite a rich collection of published training material, many have recommended a mentoring process to train clinical trialists and data scientists lacking DMC experience. We propose that academic, regulatory, industry and other leaders in clinical trials support including investigators lacking DMC experience as members of a DMC so that they can be trained to learn about the DMC processes during conduct of an actual trial”.